If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(5/6)*(1-x) = -x-1 // + -x-1
(5/6)*(1-x)+x+1 = 0
5/6*(1-x)+x+1 = 0
5/6*(1-x)+x+1 = 0
1/6*x+5/6+1 = 0
1/6*x+11/6 = 0
1/6*x+11/6 = 0
1/6*x+11/6 = 0 // - 11/6
1/6*x = -11/6 // : 1/6
x = -11/6/1/6
x = -11
x = -11
| -3m^3+3m^2=-36m | | 3(4x-7)=-129 | | -15+m=-19 | | 3+8s-5c= | | |x-2|=-2 | | -2(7+3x)=-14 | | -3/4(8p-12) | | 3a+2b-8+b= | | -3r+5=7 | | 2(4x+1)=-54 | | 6x+3=4r+11 | | -4(5x-6)=-16 | | 2/3x-32/3-7 | | 2(10+7x)=188 | | -4n-6=-2(1-3n) | | (-9p^4)(-6p^2)= | | 6x-1+4x=-21 | | 5+b=30 | | -4-1t=88 | | 1=4/1/2-1/1/3p | | 6x^4=5x^3-x^2 | | 3y=y-24 | | 3-x=-(x-3) | | 8t-3/4 | | x^2+3x+3=x^2+12 | | 1=41/2-11/3 | | 3x-8=-5x-32 | | -3x-3=-7x+15 | | 7x+9+4x=119 | | 3(x-9)=5x+3 | | 6x=-12x | | 7x+8-3x=48 |